WITHDRAWN: The Relationship between Consumption of Animal Products and Expenditure Levels with Quality of Life Scores (SF-36) by Veterinary Students in Turkey - TEKİNDAL, Mustafa Agah; ÇEVRİMLİ, Mustafa Bahadır; AKIN, Ahmet Cumhur; MAT, Burak; ARIKAN, Mehmet Saltuk; POLAT, Murat (Research Square Platform LLC, 2020)
Abstract Background: The aim of the present study is to calculate the quality of life scores (Short Form-36) of veterinary students in Turkey and review their scores in terms of different socio-demographic characteristics.Methods: 1211 students that study veterinary medicine in 26 different faculties in Turkey and were selected by stratified sampling method were asked questions concerning their consumption of and expenditures on foods of animal origin using the SF-36 questionnaire between October and December 2018.Results: Significant differences were found between SF-36 components in terms of year level, gender, accommodation status, income level and level of expenditures on foods and foods of animal origin (p<0.01). As the size of budget set aside for animal products increased, the scores in the domains physical functioning, vitality, mental health, pain and general health perception increased as well, and statistically significant differences were found (p<0.01).Conclusion: Specifically regarding the veterinary students, the low quality of life scores can be increased if they can increase their income level and consumption of foods of animal origin, which will ensure that they are energetic and have a desired level of mental and general health perceptions.
Keywords: 2. Zero hunger; 4. Education; 3. Good health